The question of the dead mistress - Copperman, E. J., 1957- (Copperman, E. J., 1957- Asperger's mystery., 2018)
"Mrs. Washburn takes on the case of a woman who thinks her husband has a ghost mistress, but Samuel's Asperger's traits mean he does not believe in ghosts"--